Yellow fever in Brazil: an analysis basead on National Health System data (Research, Society and Development, 2020)
Yellow fever is an infectious disease caused by a virus, which is transmitted by the bite of Aedes and Haemagogus. The initial symptoms that are high fever, chills, tiredness, headache, muscle pain, nausea and vomiting. Thus, the text aims to make an analysis of yellow fever in Brazil between the years 2007 and 2016, based on data made available by the Departamento de Informática do Sistema Único de Saúde – DATASUS. To achieve the objective of the reserach, bibliographic readings were carried out in order to characterize yellow fever, as well as to know what are the symptoms, treatment and prevention of the disease. We also reserach secondary quantitative data from DATATUS. In the text, basesed from data presented by the Ministério da Saúde, an outbreak of yellow fever happend in the Southeast Region of the country, between the years 2017 and 2018. Thus, the importance of the vaccine as a preventive mode and the necessary procedures for it is key for efficiency in prevention. Also, as a preventive way, especially in urban areas, the control of the breeding of the transmitting mosquito must be done, since it avoids the accumulation of standing water in water tanks, cans, tires, etc., minimizing that the female deposits her eggs and more mosquitos spreads. When developing the disease in the person there is no specific treatment, the treatment is only symptomatic, where the person must be hospitalized and rest.